Metamodel of Parametric Geometric Magnetostatic Problem Based on PGD and RBF Approaches - Boumesbah, A. E.; Tomezyk, J.; Henneron, T. (IEEE transactions on magnetics, 2023)
In order to reduce the computational time induced by solving a finite element (FE) model for a magnetostatic problem with varying geometric parameters, a parametric geometric metamodel is defined using the Proper Generalized Decomposition (PGD) approach. The mesh deformation associated with the geometric variation is implemented using the Radial Basis Functions (RBF) interpolation method. The proposed approach is applied to a variable inductance, then to a permanent magnet synchronous machine (PMSM). The results show that the PGD metamodel can accurately approximate the FE solution for the case of parametric geometric problems.